2019
DOI: 10.1111/hepr.13459
|View full text |Cite
|
Sign up to set email alerts
|

Functional glycomics: Application to medical science and hepatology

Abstract: Glycomics refers to the comprehensive analysis of glycans. Recent progress in glycotechnology enables the determination of a variety of biological functions of glycans. Among different glycosylation patterns, certain types of aberrant glycosylation are linked to cancer and/or inflammation, and thus have biological importance. Glycotechnology has been applied to many fields of medical science, including hepatology. In particular, dramatic changes in glycosylation are observed in the progression of liver disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…The mechanism that justifies the edematogenic effect of CaBo may not be clear, however, in vivo tests added to in silico analyses of the carbohydrate‐binding ability of CaBo suggests that the interaction of lectin with complex N ‐glycans contributes to the induction of the process inflammatory. It is also important to note that other studies have already reported that pro‐inflammatory cytokines induce changes in cell‐surface N ‐glycosylation of endothelial cells, suggesting that glycosylation might contribute to inflammatory vascular diseases 33 . These events suggest a double participation of CaBo's CRD in these biological processes.…”
Section: Resultsmentioning
confidence: 77%
“…The mechanism that justifies the edematogenic effect of CaBo may not be clear, however, in vivo tests added to in silico analyses of the carbohydrate‐binding ability of CaBo suggests that the interaction of lectin with complex N ‐glycans contributes to the induction of the process inflammatory. It is also important to note that other studies have already reported that pro‐inflammatory cytokines induce changes in cell‐surface N ‐glycosylation of endothelial cells, suggesting that glycosylation might contribute to inflammatory vascular diseases 33 . These events suggest a double participation of CaBo's CRD in these biological processes.…”
Section: Resultsmentioning
confidence: 77%
“…It is also known to be a marker of a hypercarcinogenic state in patients infected with the hepatitis C virus and who have achieved a sustained virologic response 7–9 . The tumor marker AFP has one N ‐glycan at Asn 232, and core fucosylation of the glycan is observed in some HCC patients 10–12 . Fucosylated AFP is known to be a marker of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation is one of the most important post‐translational modifications of proteins and lipids. Glycolipids, including sphingolipids, are formed through the addition of short sugar chains and are mostly involved in cell signaling 15 …”
Section: Introductionmentioning
confidence: 99%
“…Glycolipids, including sphingolipids, are formed through the addition of short sugar chains and are mostly involved in cell signaling. 15 Unique oligosaccharide structures are defined by the sequential reaction of glycosyltransferases and processing glycosidases. 15 In many infectious diseases caused by either viruses or bacteria, pathogen glycoproteins play important roles during the infection cycle, ranging from entry to successful intracellular replication and host immune evasion.…”
mentioning
confidence: 99%
See 1 more Smart Citation